Farm Biosecurity Measures among the Commercial Livestock and Poultry Farmers - Panda, Pratikshya; Tiwari, Rupasi; Handage, Sushant; Joshi, Pragya; Dutt, Triveni (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Animal diseases have a major impact on the livestock sector production worldwide. Infectious diseases spread in farms from environment as well as through visitors, vectors, stray animals etc. Proper biosecurity measures are known to protect the animals from various infectious or non-infectious diseases as biosecurity and animal welfare are intrinsically linked. This study was designed to investigate the existing knowledge level of commercial dairy, pig and poultry farmers regarding various biosecurity measures. Uttar Pradesh was selected purposively keeping in view its highest meat and milk production in the country. A total of 120 farmers (40 from each group, viz., dairy, pig and poultry) were selected randomly. An interview schedule was developed to collect the data. Standardised knowledge test was administered which was having 29 items under seven dimensions, viz., location and design of farm, restricted access, isolation and quarantine, cleaning and disinfection, management of feed and water, disposal of carcass, manure and waste and health management. The major findings of the study revealed that 47.50% of the respondents had medium level of knowledge regarding overall biosecurity. Dairy farmers showed comparatively lower knowledge than pig and poultry farmers. An overall knowledge gap of 24 % was estimated. Highest knowledge gap of 32% was seen in case of disposal of carcass, manure and waste. The gap can be narrowed down by imparting proper education along with creating awareness regarding biosecurity.
Keywords: Biosecurity; Dairy; Knowledge gap; Pig; Poultry